Combined Coronary Revascularization: Single-Center 10-Year Experience. Issue 1 (January 2016) - Aymami, Marie; Ruggieri, Vito Giovanni; Rouzé, Simon; Flécher, Erwan; Guihaire, Julien; Anselmi, Amedeo; Harmouche, Majid; Langanay, Thierry; Boulmier, Dominique; Roisne, Antoine; Leguerrier, Alain; Verhoye, Jean-Philippe; et al.
Abstract : Objective: This study aimed to assess the long-term outcome of combined coronary revascularization. Methods: Between January 2000 and September 2010, 106 consecutive patients underwent combined coronary revascularization, either the same day or staged within 90 days. Percutaneous coronary intervention was always performed before coronary artery bypass grafting. We identified three groups as follows: one-stop combined coronary revascularization (n = 20), percutaneous coronary intervention for acute coronary syndrome before subsequent surgery (n = 39), and percutaneous coronary intervention for stable coronary artery disease before subsequent surgery (n = 47). Off-pump technique was used in all cases. Results: A total of 107 angioplasties were realized (drug-eluting stents, 21; bare metal stents, 114; balloon angioplasty, 4). Percutaneous coronary intervention was mostly performed in the right coronary artery or branches (85%). The mean (SD) number of grafts was 1.9 (0.6), among them 1.8 (0.7) with arterial grafts. A total of 87.7% of the patients underwent exclusive arterial revascularization. There was one reexploration for bleeding and no in-hospital death. Eleven patients died in the follow-up. Repeat percutaneous coronary intervention was necessary for six patients and repeat surgery for one patient. The mean (SD) follow-up was 6.1 (2.7) years. Complete follow-up was obtained in 96.2% of the patients. Freedom from ischemic events (all-cause deaths, angina, acute coronary syndrome, myocardial infarction) was 86.3% (3.7%) at 5 years and 79.7% (5.2%) at 8 years (no difference between groups). Freedom from major adverse cardiac or cerebrovascular events was 88.8% (3.4%) at 5 years and 75.7% (5.2%) at 8 years (no difference between groups). Conclusions: Combined coronary revascularization increases the use of arterial grafts, with good long-term outcome.